A review on bio-based lubricants and their applications. (1st December 2017) - Syahir, A.Z.; Zulkifli, N.W.M.; Masjuki, H.H.; Kalam, M.A.; Alabdulkarem, Abdullah; Gulzar, M.; Khuong, L.S.; Harith, M.H.
Abstract: In transportation and industrial sectors, the world relies heavily on petroleum-based products which may cause grave concern related to future energy security. On certain cases, these products would end up back to the environment causing serious environmental pollution and hazards. Recognized as potential substitutes to mineral-based lubricants, bio-based lubricants have received growing interest as they play a significant role in overcoming above problems. Bio-based lubricants have been found to exhibit superior lubricant properties over the conventional mineral lubricants, with renewability and biodegradability being their strongest suit. There is a strong need to review the available literature to explore the potential of bio-based lubricants for various applications. In this regard, the goal of this paper is to highlight the potential of biolubricants for a broad range of applications based upon the published researches over the past decade. The correlation between molecular structures, physicochemical properties and lubrication performance of natural oil were reviewed which is essential for lubricant development and selection. This review also acknowledged some applications of which the potential use of bio-based lubricant has been explored. Based on the key findings, it can be concluded that bio-based lubricant is a promising substitute for various applications due to their availability in wide arrays of properties which are essential for some applications. However, for certain applications, prior chemical modification is required to overcome the limitations including substandard low temperature characteristics and oxidative stability. With proper base oil and additive packages formulation, bio-based lubricants can perform better than the conventional lubricants.